2012
DOI: 10.1111/j.1755-263x.2012.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing threat management for biodiversity conservation

Abstract: Calls for threat management actions to protect biodiversity and restore ecosystem function are rarely coupled with costed and prioritized sets of management actions for use in decision making. We present a cost-effectiveness approach for prioritizing threat management to maximize the in situ protection of biodiversity per dollar spent. The approach draws on empirical data and expert knowledge of major threats to biodiversity, feasible threat management actions, and likely responses of biodiversity to a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
225
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(229 citation statements)
references
References 32 publications
1
225
1
1
Order By: Relevance
“…Despite the potential for substantial and direct negative effects of dingoes on the same threatened fauna through predation [26,51,55,70], such predictions have led some to advocate cessation of dingo control programs with the expectation that doing so will provide widespread net benefits to threatened fauna at lower trophic levels (e.g. [13,32,71]). However, our simultaneous assessment of the effects of dingo control on predator and prey populations demonstrated that the predicted mesopredator increases do not occur (Table 5 and because contemporary dingo control practices "do not appear to suppress dingo populations to levels low enough and long enough for mesopredators to exploit the situation" ( [25], pg.…”
Section: Trophic Cascade and Mesopredator Release Theory And Realitymentioning
confidence: 99%
“…Despite the potential for substantial and direct negative effects of dingoes on the same threatened fauna through predation [26,51,55,70], such predictions have led some to advocate cessation of dingo control programs with the expectation that doing so will provide widespread net benefits to threatened fauna at lower trophic levels (e.g. [13,32,71]). However, our simultaneous assessment of the effects of dingo control on predator and prey populations demonstrated that the predicted mesopredator increases do not occur (Table 5 and because contemporary dingo control practices "do not appear to suppress dingo populations to levels low enough and long enough for mesopredators to exploit the situation" ( [25], pg.…”
Section: Trophic Cascade and Mesopredator Release Theory And Realitymentioning
confidence: 99%
“…trapping, hunting, or poisoning) must be banned in order to generate cascading, positive effects on biodiversity (e.g. Carwardine et al, 2012), information on the actual effects of carnivore hunting or poisoning on biodiversity are needed, not just information on how one carnivore species might interact with another (for examples, see . Conversely, when claiming that large carnivore control must be implemented to reduce livestock predation, information on actual carnivore impacts and impact reduction is required to ethically justify carnivore control (Braysher, 1993;Allen et al, 2014b;Allen, 2017).…”
Section: There Is a Dearth Of Applied-science Studiesmentioning
confidence: 99%
“…Moreover, current methods commonly require experts to estimate the likely benefits of candidate management strategies using direct, probabilistic judgements (the 'probability of persistence' of a species; e.g. Carwardine et al, 2012;Joseph et al, 2009), which can be prone to error and bias (Lagnado & Sloman, 2004;O'Hagan et al, 2006;Bolger & Wright, 1994).…”
Section: Parks Vol 231 March 2017mentioning
confidence: 99%
“…These approaches can include simple spreadsheet methods where the benefits of alternative management strategies are divided by their cost (e.g. Auerbach et al, 2014;Carwardine et al, 2012), algorithms which iteratively remove low-ranking strategies and update cost-efficiency rankings (e.g. Joseph et al, 2009;Chadés et al, 2015), and spatially explicit systematic conservation planning software that solve integer programming problems (e.g.…”
Section: Parks Vol 231 March 2017mentioning
confidence: 99%